Menilik Peran Pesantren dan Madrasah dalam Menangkal Radikalisme di Indonesia - Arif Syamsurrijal (Al Hikmah: Jurnal Studi Keislaman, 2021)
Education, both formal and non-formal, has a very vital role in the process of deradicalization in Indonesia. However, education can also be a forum for radicalism to emerge, considering that there are several schools that are made "different" with certain concepts to instill radicalism. This article provides a description to see how Islamic boarding schools and madrasas in Indonesia counteract radicalism in Indonesia. Islamic boarding schools are traditional Islamic educational institutions that exist to understand, appreciate and practice the teachings of the Islamic religion (tafaqquh fiddin) by emphasizing religious morals as guidelines for daily life in society. Pesantren is the oldest educational institution in Indonesia which has an important contribution in educating the nation's life. This institution deserves to be taken into account in the development of the Indonesian nation in the fields of education, religion and morals. Viewed historically, pesantren have had extraordinary experiences in fostering, educating and developing the community around them. Keywords: pesantren, madrasah, radicalism